Diversity and abundance of pest mites (Acari: Tetranychidae) on papaya in Tanah Laut and Banjarbaru City, South Kalimantan, Indonesia - Pramudi, Muhammad Indar; Helda Orbani Rosa,; Hamidah, (Pusat Sistematik Serangga, Universiti Kebangsaan Malaysia, 2022)
Information on the diversity and abundance of mites on papaya in South Kalimantan is still limited and needs further study. Thus, a study was conducted in Banjarbaru and Tanah Laut, South Kalimantan, Indonesia on three varieties of papayas (California, Hawaii, and Merah Delima). Four species of mites that attacked papayas in Banjarbaru were identified as Tetranychus piercei, Aculops pelekassi, Brevipalpus phoenicis, and Eutetranychus africanus, while in Tanah Laut T. piercei and E. africanus. Tetranychus piercei with 2557 individuals was the most abundant at both locations. Tetranychus piercei was found to be in the highest number observed on papayas varieties, while A. pelekassi was found on Hawaii varieties with 13 individuals, E. africanus on California varieties with nine individuals, and B. phoenicis with only eight individuals on Hawaiian varieties. The diversity index value (H’) of mites at the research areas was low (H'<1.5) indicated the communities formed were less stable (H'<1) probably under pressure. The species dominance index (C) value was significantly close to 1 (≥0.5), and indicative of certain species dominated (in this study was T. piercei) at the two research sites. The results of this research could provide important information about mites and be useful as the first step in developing effective pest control strategies.